Analysis of Excavated Slope Stability on the TRSS of Blitar Regency with a Cracked Soil Approach - Muhammad Arifian Ilham; Herman Wahyudi; Yudhi Lastiasih (Interdisciplinary Social Studies, 2025)
The construction of the Southern Cross Line (JLS) in East Java Province is part of the National Strategic Project which aims to reduce the disparity between the northern and southern regions of Java Island. In STA 17 + 850 of the Bululawang–Sidomulyo–Tambakrejo section, the excavated slope of ±30 m high composed of limestone rocks experienced two landslides in the same segment (slope 2 and slope 3), although slope geometry has been improved through regrading from a slope of 71.6° to 45°. This study aims to analyze the main causes of landslides at the location using the cracked soil approach, as well as evaluate the effect of slope slope on the safety factor (SF) value. The concept of cracked soil refers to the existence of cracks, it can be in the form of fine cracks that are not visible visually or wide cracks, these cracks can function as rainwater infiltration pathways that can trigger collapse. The soil condition on the slope is modeled as a "behaving like sand" material with a "drained" condition (c = 0 and ? = ?). The analysis method was carried out using the Finite Element Method (FEM) with the Plaxis 2D auxiliary program through two main models. Model 1 models the soil material to be "behaving like sand" (c = 0 and ? = ?), so that the collapse is completely controlled by the inner shear angle in the absence of cohesion. Model 2 includes a polygon such as ground cracks placed on or near a slip plane, thus facilitating a specific c = 0 on that plane with variations in the width and depth of the cracks. Stability analysis at the initial conditions (after excavation) showed an SF value of >> 1, which did not yet represent the landslide conditions in the field. Through the cracked soil approach, an SF value of < 1 was obtained for both slope slope variations, both in model 1 and model 2. These results show that the cracked soil approach can be applied to explain the mechanism of landslides on the slope of STA 17 + 850 of the Bululawang-Sidomulyo-Tambakrejo Section.